Improving the Efficiency of Online Retail Activities for Merriman Brand of Hoa Tho Textile - Garment Joint Stock Corporation Company - Vo, Thi Suong (Vietnam - Korea University of Information and Communication Technology, 2023)
Graduation thesis of Business Administration